Pewien Przypadek Nieustalonego Rozkładu Temperatury w Długim Walcu - Różnowski, T. (Engineering Transactions, 1965)
A half of the lateral surface of the cylinder is assumed to have been heated suddenly to a temperature varying according to the graph of the trapezoidal form along the lateral surface. At t > 0 the given temperature field starts moving with constant velocity v. The problem has been solved by means of integral transformations. The results are represented in the form of series of Bessel and error functions, the values of the integrals being taken from the tables. The temperature function is analysed in sections passing through the front of the moving temperature field and through the edge of the trapezoidal form. Some particular cases are considered.